1994
DOI: 10.1177/089124249400800408
|View full text |Cite
|
Sign up to set email alerts
|

"Ties that Bind" Reexamined

Abstract: Correlations between indicators of economic success of central cities and their suburbs have been used as evidence that the suburbs depend on central cities for economic development. This article revisits the suburban dependency thesis by considering the supposition that state-level variables contribute to the success of both central city and suburbs. Thus the correlations between central cities and suburban indicators of development may be due to the fact that both are influenced by state-level activities rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…In this article, we replicate previous research (i.e., Barnes and Ledebur 1998;Savitch et al 1992;Voith 1992Voith , 1993Blair and Zhang 1994) that demonstrates a relationship between the change in central-city and suburban per capita income. We then determine the extent of the state economy's influence on the urban-suburban relationship (Blair and Zhang 1994). We also examine an important condition underlying several proposed remedies for the economic disparity between central cities and their suburbs.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…In this article, we replicate previous research (i.e., Barnes and Ledebur 1998;Savitch et al 1992;Voith 1992Voith , 1993Blair and Zhang 1994) that demonstrates a relationship between the change in central-city and suburban per capita income. We then determine the extent of the state economy's influence on the urban-suburban relationship (Blair and Zhang 1994). We also examine an important condition underlying several proposed remedies for the economic disparity between central cities and their suburbs.…”
supporting
confidence: 87%
“…Drawing on these findings, some researchers have suggested that incentives to foster regional cooperation and governance are not only desirable but also are in the self-interest of central cities and their suburbs (Barnes and Ledebur 1998). Others caution against interpreting these empirical findings to mean that metropolitan-area economic growth is enhanced by reducing economic disparities between central cities and their suburbs and that regionalism should be promoted as a strategy for metropolitan economic growth (Blair and Zhang 1994;Hill, Wolman, and Ford 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…62, No. 3, Summer 1996 (Garreau 1991;Persky, Sclar, and Wiewel S 1991;Ledebur and Barnes 1992;Voith 1992;Savitch 1993;Blair and Zhang 1994;Hill, Wolman, and Ford in press). David Rusk's (1993) Cities Without Suburbs is the latest important contribution to this literature.…”
mentioning
confidence: 99%
“…At the within-metropolitanarea level, much of the past research has taken into account a metropolitan area as an integrated domain of the local labour market, in which income change between the central city and its suburban ring is interdependent and highly correlated in the same direction (Hill et al, 1995;Ledebur and Barnes, 1992;Voith, 1998); the urban job mismatch argument stresses the growing central-citysuburban disparity in job opportunities that often causes more adverse outcomes for the city's African Americans (Browne, 2000;Stoll et al, 2000); employment suburbanisation due to central-city economic hardship ultimately accelerates the central-city-suburban status difference (Mieszkowski and Mills, 1993;Wilson, 1996), and the economic dominance of central city weakens economically relative to its surrounding suburban ring, eventually operating as a dormitory community (Hughes, 1993;Madden, 2000). On the other hand, the contrary argument is that the two independent economic entities within a metropolitan area ultimately co-exist with the gradual autonomy of the suburban economy over the central-city infl uence (Baldassare, 1992;Blair and Zhang, 1994;Mueller, 1997;Swanstrom et al, 2006). No matter what patterns of economic relationship exist between the central city and its suburban ring within a metropolitan area, it seems clear that spatial location is a critical ingredient in the analysis of both metropolitan and intrametropolitan economic volatility (Reiss, 1956).…”
Section: Spatial Economic Factorsmentioning
confidence: 99%